Evaluation of the Possible Relationship between the Curvature and Horizontal Course of the Inferior Alveolar Canal - Koca, Cansu G.; Cicek, M. F.; Sadry, Sanaz; Yenidunya, Ozan; Kaplan, Fatma Akkoca; Erdil, Aras (Current Medical Imaging, 2023)
Objectives: The position of the inferior alveolar canal (IAC) and its course in the mandible is crucial to prevent complications in oral surgical procedures. Therefore, the present study aims to predict the course of IAC using landmarks specific to the mandible and to correlate with cone-beam computed tomography images. Methods: On the included panoramic radiographs (n=529), the closest point of the IAC to the inferior border of the mandible (Q) was determined, and the distances of this point to the mental (Mef) and mandibular foramen (Maf) were measured in millimeters. To determine the buccolingual course of the IAC on CBCT images (n=529), the distances from the center of the canal to the buccal and lingual cortices and between the cortices were measured at the level of the root apices of the first and second premolars and molars. Also, the positions of the Mef to adjacent premolars and molars were classified. Results: The most common position of mental foramen was Type-3 (37.1%). On the coronal plane, it was also observed that as the Q point approaches the Mef, the IAC is located in the mandible's center at the second premolar level (p=0.008) and moves away from the midline at the level of the first molar (p=0.007). Conclusion: Based on the results, a correlation was observed between the horizontal course of the IAC and its proximity to the inferior border of the mandible. Therefore, the curvature of the IAC and its proximity to the mental foramen should be considered in oral surgeries.
Keywords: radiographs